2018
DOI: 10.3389/fncel.2018.00120
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hair Cell Regeneration Is Prevented by Increased Notch Signaling in Supporting Cells

Abstract: During embryonic development, differentiation of cochlear progenitor cells into hair cells (HCs) or supporting cells (SCs) is partially controlled through Notch signaling. Many studies have shown that inhibition of Notch signaling allows SCs to convert into HCs in both normal and drug damaged neonatal mouse cochleae. This mechanism is also implicated during HC regeneration in non-mammalian vertebrates; however, the mechanism of spontaneous HC regeneration in the neonatal mouse cochlea is less understood. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 68 publications
(125 reference statements)
2
25
0
Order By: Relevance
“…Thus, when N1ICD is expressed as hair cells begin to differentiate, hair cells begin to upregulate supporting cell-specific genes and the animals become functionally deaf with the hair cells dying, but if N1ICD is expressed in hair cells after they differentiate, they become largely unresponsive to Notch signaling-induced fate changes, upregulating the supporting cell genes Sox2 and Prox1, but otherwise showing no other detectable effects on hair cell maturation [95,96]. Over-expression of N1ICD in supporting cells of neonatal mice also reduces the spontaneous regeneration of hair cells that can occur in early postnatal life [97]. Loss of Notch1, Dll1, Jag2, or other Notch pathway genes during hair cell differentiation results in the generation of supernumerary hair cells (see Table 1), as does the inhibition of gamma secretases through pharmacological agents like DAPT [61,90].…”
Section: A Future For Notch? Notch Signaling In the Inner Ear After Smentioning
confidence: 99%
“…Thus, when N1ICD is expressed as hair cells begin to differentiate, hair cells begin to upregulate supporting cell-specific genes and the animals become functionally deaf with the hair cells dying, but if N1ICD is expressed in hair cells after they differentiate, they become largely unresponsive to Notch signaling-induced fate changes, upregulating the supporting cell genes Sox2 and Prox1, but otherwise showing no other detectable effects on hair cell maturation [95,96]. Over-expression of N1ICD in supporting cells of neonatal mice also reduces the spontaneous regeneration of hair cells that can occur in early postnatal life [97]. Loss of Notch1, Dll1, Jag2, or other Notch pathway genes during hair cell differentiation results in the generation of supernumerary hair cells (see Table 1), as does the inhibition of gamma secretases through pharmacological agents like DAPT [61,90].…”
Section: A Future For Notch? Notch Signaling In the Inner Ear After Smentioning
confidence: 99%
“…Some have hypothesized that Lgr5positive SCs are the progenitor cells within the neonatal mouse cochlea (Bramhall et al, 2014;Chai et al, 2012;McLean et al, 2017;Shi et al, 2012;Shi et al, 2013;Waqas et al, 2016); however, the Lgr5-postive population includes different subtypes of SCs, and the expression of Lgr5 changes dynamically during the first postnatal week (Chai et al, 2011;Shi et al, 2012). In addition, we have recently shown that spontaneous HC regeneration in vivo can be prevented by increased Notch signaling (McGovern et al, 2018), which suggests that the SC subtypes that respond to changes in Notch signaling after HC damage contribute to spontaneous regeneration.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, evidence has emerged that the neonatal mouse cochlea has a limited period in which it is capable of spontaneously regenerating HCs after they have been destroyed, both in vivo (Cox et al, 2014;Hu et al, 2016;McGovern et al, 2018) and in vitro (Bramhall et al, 2014). To demonstrate that regeneration had occurred, broad populations of SCs were fate-mapped using either Hes5 lacZ knock-in reporter mice, Lgr5 CreER ::Rosa26 tdTomato mice or Sox2 CreERT2 ::Rosa26 tdTomato mice (Bramhall et al, 2014;Cox et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Lgr5-expressing cells in the neonatal cochlea possess a latent potential to proliferate and to convert into hair cells (Cox et al 2014; Stone and Cotanche 2007). This mitotic regeneration has been explored in supporting cells as a potential avenue for hair cell regeneration with Wnt activation and Notch signaling playing roles in supporting cell conversion into hair cells (Ni et al 2016; McGovern et al 2018, 2019). Consistent with these observations, protein interaction analyses suggest potentially relevant interactions between Notch signaling and Wnt signaling pathways and cell cycle control, specifically Cdkn1b (Figure 6G).…”
Section: Discussionmentioning
confidence: 99%